Comparison of calcium bioaccessibility in cow’s milk, sesame seeds (Sesamun indicum) and almond (Prunus amygdalus) - Damián Bastidas, Narda Lucía (2021)
Introduction. The bioavailability of a nutrient reflects the fraction available to be absorbed and used. Is critical when evaluating the nutritional quality of a food. Objective. To compare the bioaccessibility of calcium between sesame (Sesamun indicum) and almond (Prunus amygdalus) with the bioaccessibility of calcium from cow’s milk using an in vitro method. Methods. An observational study that evaluated bioaccessibility using the in vitro dialyzability method. Results. Calcium dialysability of cow’s milk was 20,71%; in sesame and almond seeds it was 1% and 2,27%, respectively. It was determined that cow’s milk covers between 2% - 4% of the total calcium requirement in children 1 to 6 years of age and 2% in adolescents and adults. In seeds the coverage was minimal. Conclusions. The bioaccessibility and potential calcium contribution of whole cow’s milk was higher compared to almond and sesame seeds.